Eduard Steuermann »Musiker und Virtuose«: Symposiumsbericht - Laubhold, Lars E. (Edition Text + Kritik, 2022)
Eduard Steuermann (1892-1964), Austrian-Polish-Jewish pianist from Galicia, student of Busoni, teacher and friend of Adorno, exiled American, sought-after soloist and pedagogue between Vienna, New York and Darmstadt, sought throughout his life the "almost impossible": to reconcile truth and beauty in uncompromising "devotion to music". The esteem in which he was held as the most important pianist for the establishment of New Piano Music, not only by the Viennese Schoenberg circle, has had a lasting effect on an appreciation of his person that goes beyond this. In 14 contributions that look at Steuermann from very different angles - discussing his life, his family and artistic ties, his music-making and composing, his work as a teacher and witty author - the view of the breadth of his work is widened on the basis of numerous previously unexplored materials, and the portrait of an artist who, according to Adorno, embodied the "conscience" of music itself is drawn.